Investigating Customer Feedback on BNIFX's New Product at PT. Bank Negara Indonesia (Persero) Tbk. Jakarta Senayan - Hendrawan, Hariadi (Devotion : Journal of Research and Community Service, 2023)
The Covid-19 pandemic demands that banking technology services become a necessity and are increasing. This is captured as a very good opportunity for PT. Bank BNI (Persero) Tbk. The Jakarta Senayan area s taking strategic action, namely on 23 August 2021 launching a new digital-based product, namely BNIFX. The problem is that until 2022, out of 4,081 customers in the wholesale group, which is the main segment, only 3 (three) customers have transacted through BNIFX (0.0007%). The study aims to investigate the factors that encourage and reject customers to make transactions on BNIFX products, as well as investigate strategies carried out by the management of possible risks of rejection of BNIFX product. This type of research uses a qualitative design, the main data source obtained by open interviews. The results of this study obtained the concept that: (1). For those who have used BNIFX because the data becomes very real time, time is more efficient and effective, cut off, pricing and trust. Related to this, there is no significant added value. (2). The main reason for those who haven't used BNIFX is because they are afraid of adapting to the new system, so the product that is more in demand is BNI direct. (3). The main strategy undertaken is to optimize a very wide network of branch offices (both domestic and overseas), increase knowledge for potential customers, improve promotion techniques.